PENGARUH KOMPETENSI DAN KOMPENSASI TERHADAP KINERJA MELALUI MOTIVASI PNS SEKRETARIAT DPRD KOTA PROBOLINGGO - Ismarini, Ismarini (MAP (Jurnal Manajemen dan Administrasi Publik), 2024)
The purpose of this study was to determine the Effect of Competence and Compensation on Performance through Motivation in the Secretariat Employees of the Probolinggo Municipal DPRD. The sampling technique used is simple random sampling method with a total population and sample of 35 employees of the Probolinggo Municipal DPRD Secretariat. Collecting data by distributing questionnaires to respondents. This type of research uses quantitative methods with data analysis using the SmartPLS 4.0 application. The results of the study show that: 1) Competence, compensation, motivation and performance of employees of the Probolinggo Municipal DPRD Secretariat are in the good category. 2) Competence has a significant effect on the Performance of Probolinggo Municipal DPRD Secretariat Employees. 3) Competence has a significant effect on the Motivation of Probolinggo City DPRD Secretariat Employees. 4) Compensation has a significant influence on the Performance of Probolinggo Municipal DPRD Secretariat Employees. 5) Compensation has no significant effect on the Motivation of Probolinggo Municipal DPRD Secretariat Employees. 6) Motivation has a significant influence on the Performance of Probolinggo Municipal DPRD Secretariat Employees. 7) Competency have a significant influence on Performance through the Motivation of Probolinggo Municipal DPRD Secretariat Employees. 8) Compensation has no significant effect on Performance through Motivation of Probolinggo Municipal DPRD Secretariat Employees.